Mechanochemical Catalytic Transfer Hydrogenation of Aromatic Nitro Derivatives - Tomislav Portada; Davor Margetić; Vjekoslav Štrukil (Molecules, 2018)
Mechanochemical ball milling catalytic transfer hydrogenation (CTH) of aromatic nitro compounds using readily available and cheap ammonium formate as the hydrogen source is demonstrated as a simple, facile and clean approach for the synthesis of substituted anilines and selected pharmaceutically relevant compounds. The scope of mechanochemical CTH is broad, as the reduction conditions tolerate various functionalities, for example nitro, amino, hydroxy, carbonyl, amide, urea, amino acid and heterocyclic. The presented methodology was also successfully integrated with other types of chemical reactions previously carried out mechanochemically, such as amide bond formation by coupling amines with acyl chlorides or anhydrides and click-type coupling reactions between amines and iso(thio)cyanates. In this way, we showed that active pharmaceutical ingredients Procainamide and Paracetamol could be synthesized from the respective nitro-precursors on milligram and gram scale in excellent isolated yields.